A Population Genomics Approach to Assessing the Genetic Basis of Within-Host Microevolution Underlying Recurrent Cryptococcal Meningitis Infection. Issue 4 (1st April 2017) - Rhodes, Johanna; Beale, Mathew A; Vanhove, Mathieu; Jarvis, Joseph N; Kannambath, Shichina; Simpson, John A; Ryan, Anthea; Meintjes, Graeme; Harrison, Thomas S; Fisher, Matthew C; Bicanic, Tihana
Abstract: Recurrence of meningitis due to Cryptococcus neoformans after treatment causes substantial mortality in HIV/AIDS patients across sub-Saharan Africa. In order to determine whether recurrence occurred due to relapse of the original infecting isolate or reinfection with a different isolate weeks or months after initial treatment, we used whole-genome sequencing (WGS) to assess the genetic basis of infection in 17 HIV-infected individuals with recurrent cryptococcal meningitis (CM). Comparisons revealed a clonal relationship for 15 pairs of isolates recovered before and after recurrence showing relapse of the original infection. The two remaining pairs showed high levels of genetic heterogeneity; in one pair we found this to be a result of infection by mixed genotypes, while the second was a result of nonsense mutations in the gene encoding the DNA mismatch repair proteins MSH2, MSH5, and RAD5 . These nonsense mutations led to a hypermutator state, leading to dramatically elevated rates of synonymous and nonsynonymous substitutions. Hypermutator phenotypes owing to nonsense mutations in these genes have not previously been reported in C. neoformans, and represent a novel pathway for rapid within-host adaptation and evolution of resistance to first-line antifungal drugs.